Programmable materials for efficient CTCs isolation: From micro/nanotechnology to biomimicry. Issue 6 (16th May 2021) - Hou, Jianwen; Liu, Xia; Zhou, Shaobing
Abstract: Escaping from primary tumors and entering into blood flow, circulating tumor cells (CTCs) contain significant information for both the original tumors and metastasis mechanisms. CTCs detection has become an effective liquid biopsy of tumors and shows great promise in early cancer detection, disease monitoring, prognosis and personalized medicine. Despite the urgent need from clinics, CTCs isolation from blood is still a huge challenge due to their extreme rareness in blood. Well‐defined micro/nanostructures and nature‐inspired hierarchical architectures offer unique avenues to address this challenge by matching well with the special physical properties of CTCs to sort cells or forming local topographic interactions to strengthen cell adhesion, thereby improving the CTC‐isolation performance. In this review, we first summarize researches on CTCs isolation with diverse micro/nanostructured substrates, which mainly include nanomaterials, microfluidics, DNA nanostructures, micromotors and in vivo detection devices. In sequence, various CTC‐isolation biomimetic architectures, which are inspired by different natural creatures (e.g., viruses, cells, extracellular matrix [ECM], plants, and animals), have been highlighted. At last, remaining challenges and future perspectives in designing CTC‐isolation platforms for clinical applications are also discussed. Abstract : The progress in CTCs isolation achieved by various multiscale biomimetic architectures is summarized. The remaining challenges and future perspectives in designing CTC‐isolation platforms in clinical applications are also discussed.